Bluetongue virus serotype 12 enters Australia – a further incursion of novel western lineage genome segments. (17th March 2021) - White, John R.; Williams, David T.; Davies, Kelly; Wang, Jianning; Chen, Honglei; Certoma, Andrea; Davis, Steven S.; Weir, Richard P.; Melville, Lorna F.; Eagles, Debbie
Abstract : Bluetongue virus (BTV) is an arbovirus (genus: Orbivirus ) that occurs worldwide. It infects domestic and wild ruminant species and can cause disease in livestock, producing high economic impact. Recently, it gained extra prominence throughout Europe, with disease occurring in regions traditionally free of BTV. BTV enters Australia from Southeast Asia via wind-borne infected Culicoides spp. The first Australian isolation was 1975 (BTV-20) and further serotypes were isolated between 1979–86 (BTV-1, -3, -9, -15, -16, -21, -23). Despite increased, more sensitive, monitoring, no more were detected in over two decades, implying a stable BTV episystem of eastern ancestry. Isolations of BTV-2, -7 and -5 then occurred between 2007–15, with the latter two possessing genome segments with high sequence identity to western isolates. We report on the first isolation and genomic characterization of BTV-12, which revealed that three more novel western topotype gene segments have entered northern Australia.